2020
DOI: 10.1515/chem-2020-0088
|View full text |Cite
|
Sign up to set email alerts
|

Withania frutescens: Chemical characterization, analgesic, anti-inflammatory, and healing activities

Abstract: Withania frutescens (W. frutescens) is a medicinal plant that is largely used in the Morrocan pharmacopeia for disease treatment. This work was conducted to investigate the chemical characterization, analgesic, anti-inflammatory, and healing activities of W. frutescens. The chemical characterization of W. frutescens extract was done using HPLC; the anti-inflammatory test was performed with doses 300, 400 and 450 mg/kg, and the healing activity was assessed using two creams (extract 5% and extract 10%). Phytoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 21 publications
(25 reference statements)
2
16
0
Order By: Relevance
“…Based on previous pharmacological tests and a toxicity study, two doses (200 and 400 mg/kg) were chosen as the lowest most effective doses to treat the mice with induced diabetes [ 12 , 19 ]. Figure 1 presents the treatment’s effect on fasting blood glucose (FBG) during the study period of 4 weeks of daily oral administration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous pharmacological tests and a toxicity study, two doses (200 and 400 mg/kg) were chosen as the lowest most effective doses to treat the mice with induced diabetes [ 12 , 19 ]. Figure 1 presents the treatment’s effect on fasting blood glucose (FBG) during the study period of 4 weeks of daily oral administration.…”
Section: Resultsmentioning
confidence: 99%
“…After the treatment of diabetic mice with different doses of WFLE, a significant decrease in ASAT and ALAT levels compared to those of the diabetic control groups was observed. The results may indicate a potential hepatoprotective activity of the extract maybe due to its antioxidant, anti-inflammatory and healing proprieties [ 9 , 19 ]. High levels of urea and creatinine in the blood were also observed in the diabetic untreated groups indicating a renal injury [ 24 ], and by administering WFLE to diabetic mice, their levels were normally maintained.…”
Section: Resultsmentioning
confidence: 99%
“…W. frutescens.L extracts have been found to be rich in withanolides, which were isolated from the plant leaves. Moreover, the chemical analysis of the W. frutescens.L extract showed that this plant possessed pentacarbonyl (13.22%), 2-phenazine carbonitrile (10.64%), Terpinenol-4 (10.04%), 4H-1-benzopyran-4-one,2,3-dihydro-5,7-dihydroxy-2phenyl(S) (8.76%), and bicyclo [3.1.1]heptane, 6,6-dimethyl-2-methylene (28.48%) [20,21]. Earlier works showed no toxic effects in animals treated with the W. frutescens extract, therefore, the studied plant was considered safe in animals treated under both acute and subacute toxicity conditions [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Animals had free access to standard pellets and water during the whole period of dosing except the fasting period. This research work was revised and authorized by the ethical committee of the Faculty of Sciences of Fez and given the ethical clearance N-ANI-BPRN-1382.5 [12]…”
Section: Experimental Animalsmentioning
confidence: 99%
“…Medicinal plants have been used as an extensive medication source to control disease since more than 80% of populations use medicinal plants to fulfill their primary health care needs [11]. A variety of active ingredients have been purified from plants for direct use as medicines or to function as lead compounds or drug candidates [12].…”
Section: Introductionmentioning
confidence: 99%